Hole's essentials of human anatomy and physiology - Shier, David (McGraw-Hill, 2006)
Study guide with chapters corresponding directly to Hole's Essentials of Human Anatomy and Physiology, 8th edition, c2003. Provides chapter objectives, chapter overview, focus questions, mastery tests, and study activities.